Communication Strategy Practices and Performance of The County Government of KISII - Fred, Nyausi Oginda; Juma, Dennis; Bichanga, Julius Miroga (European Journal of Applied Sciences, 2024)
Today’s world is changing with time and managers in any institution must prepare for its effect on the organizational performance. Organizations are facing a very stiff competition by the technological advances therefore they need to adopt to change order to remain relevant. It is on this basis that the study wanted to evaluate the effect of communication strategy on performance of the County Government of Kisii. The study would be of significance to county leaders know and comprehend the significance of workplace change management methods hence developing polices leading to better performance. Literature review of the studies was either directly or indirectly related to the study. This study used positivistic paradigm with a survey research design as it assumes quantitative data using questionnaires. The study was anchored on Learning Organizational Model. The target population consisted of all heads of departs and departmental employees. This study utilized the Yamene (1967) formula in establishing the sample from the study population. Questionnaires were used to collect from staff of various departments. The pilot test was done in the neighboring Nyamira County which bears similar characteristics with the study area and were not involved during the actual data collection process. Reliability of the study tools with an alpha coefficient with a value of 0.7 and above, were considered reliable enough for data collection. Data from the questionnaires was sorted for completeness, coded and entered into the Statistical Package for Social Sciences, Version 27.0, for analysis. Analysis was then run using both descriptive and regression analysis and presented in tables and figure were applicable. The study findings revealed that communication strategy practices in Kisii County is an insignificant predictor of organizational performance. Finally, the study concludes that, communication strategy is an insignificant negative predictor organizational performance in Kisii County. It was recommended that since communication strategy is insignificant predictor of organizational performance, the county government should invest heavily on communication strategy if their have to record some significant performance.